(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Epidural anaesthesia is a commonly used neuraxial technique, and accurate identification of the epidural space is essential for successful block placement. Skin-to-lumbar epidural depth varies among individuals and may be influenced by demographic and anthropometric factors. Understanding these correlations may improve prediction of epidural depth and increase first-attempt success rates. Methodology: This hospital-based observational cross-sectional study was conducted in the Department of Anaesthesiology, Sree Mookambika Institute of Medical Sciences, Kulasekharam, from April 2025 to February 2026. Patients aged 18–70 years belonging to ASA physical status I and II undergoing elective surgeries requiring lumbar epidural anaesthesia were included. Demographic data and anthropometric measurements including height, weight, and body mass index (BMI) were recorded. Epidural depth was measured using standard loss of resistance technique. Statistical analysis included Pearson’s correlation and multivariate regression analysis. Results: A significant positive correlation was observed between body weight and epidural depth as well as BMI and epidural depth. Age, sex, and height did not show significant correlation. Regression analysis revealed that body weight and gender were significant predictors of epidural depth, explaining 68.7% of variability (R² = 0.687). Weight showed the strongest association with epidural depth. Conclusion: Body weight and gender are significant predictors of lumbar epidural depth, and their use may improve pre-procedural estimation and success of epidural anaesthesia.